How institutional frameworks impact on political representation - the case of sub-local government in Munich - Decker, H.M. (2016)
This thesis examines how institutional frameworks impact on political repre-sentation. It looks at the links and relationships that exist between political institutions and political representation, and explores how institutions shape the role and behaviour of elected representatives.